Quantitative analysis of the concentrations of IGFs and several IGF‐binding proteins in a large fibrous abdominal tumor and the circulation of a patient with hypoglycemia. (13th June 2015) - van Doorn, Jaap; van de Hoef, Wouter; Dullaart, Robin P. F.
Abstract The syndrome of nonislet cell tumor induced hypoglycemia (NICTH) represent extreme cases of excessive expression and production of incompletely processed high‐molecular‐mass pro‐IGF‐II forms (big IGF‐II) by an often large tumor. Tumor‐derived big IGF‐II is responsible for enhanced insulin‐like effects in the body through complicated mechanisms, leading to hypoglycemia. Case studies on NICTH usually focus on measurements of diagnostic parameters in the circulation of patients. Some studies have also reported on qualitative immunohistochemical analysis of tumor tissue, in particular with respect to the expression of IGF‐II at the mRNA or protein level. However, quantitative data on the concentrations of IGFs and IGFBPs in tumor specimen causing NICTH, in relation to their corresponding plasma levels are lacking. Such an analysis would provide an estimate of the total potential of (big) IGF‐II retained by the tumor and more insight in the relative levels of different IGFBPs and their origin in the circulation, that is, systemically induced by tumor related factors or directly tumor‐derived. Here we investigated quantitatively the levels of IGFs and IGFBPs in a large, 1.76 kg weighing, solitary fibrous tumor from a typical case of NICTH using highly specific immunometric assays. Besides a high level of big IGF‐II, patient's plasma also contained increased levels of both IGFBP‐2 and ‐6 which declined after removal of the tumor. These IGFBPs have a higher affinity for (pro‐) IGF‐II than IGF‐I and exhibit intrinsic IGF‐independent bioactivities. Tumor tissue contained high amounts of big IGF‐II and IGFBP‐6, exceeding that in patient's circulation many‐fold. A relatively low tumor content of IGFBP‐2 was found suggesting that the preoperative high levels in plasma were attributable to systemic mechanisms. The background literature and possible implications of these findings are briefly discussed. Based on the present results we postulate that tumor tissue is not the source of the elevated levels of IGFBP‐2 often seen in NICTH patients. Large tumors that cause NICTH can produce IGFBP‐6 leading to enhanced levels of this IGFBP in the circulation. Hence, the measurement of IGFBP‐6 in plasma may serve as an additional marker of this disease pattern. © 2015 BioFactors, 41(3):183–189, 2015